Penghayatan Orang Muda Katolik Asrama Santo Stefanus Tentang Makna Persekutuan Dalam Kehidupan Menggereja - Sinaga, Rotua Dominika (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
The purpose of this research is to see the extent of the appreciation of Catholic Youth Dormitory St. Stefanus Waena Jayapura about fellowship in church life. The method used in this research is descriptive qualitative. Primary data used in the study were interviews and observations. Unstructured interviews were conducted with dormitory coaches and Catholic young people living in St. Stephen's dormitory Waena Jayapura. The researcher used participant observation because the researcher lived at the research location. Based on the findings and discussion of this research, the Catholic Young People of St. Stephen's Dormitory Waena live communion in church life as far as the desire to gather and tell stories to build good communication. Gathering and telling stories are ways for young Catholics in the St. Stefanus Waena dormitory to live communion in church life. On the other hand, researchers found that there are obstacles in the effort to live communion that come from within the young people themselves and also from outside themselves. The obstacles found are low awareness, self-adjustment, initiative and knowledge about the Eucharist and Church activities. Low awareness is due to the lack of family role to transform values to build communion in church life so that it is less likely to reach the level of internalization or appreciation as expected.